Evaluation of the PID-5 depressivity personality dimensions and depressive symptomatology in a community sample - Gonçalves, Bruno; Pires, Rute; Henriques-Calado, Joana; Sousa Ferreira, Ana (Anales de Psicología / Annals of Psychology, 2022)
The alternative model for the classification of personality disorders presented in the DSM-5 is based on the hypothesis of continuity between normal personality and personality disorders. The main objective of this study is to analyze the relationship between depressive symptomatology and the domains and facets of the PID-5, especially the Depressivity facet. A convenience sample of the general population (N = 453) was used. Participants responded to the PID-5 and the CES-D. In a multiple regression model including all the PID-5 facets, only Depressivity and Anhedonia had a significant individual effect on predicting the CES-D score. Correlation analysis suggested that Depressivity and Anhedonia could be considered as defining the depressive traits of personality disorders and supported the continuity between these disorders and depressive symptomatology. A Taxometric Analysis with the Depressivity facet and CES-D score as indicators supported the dimensional nature of depressivity in a broad sense (depressive traits/ depressive symptomatology).